Pembiasaan Diri Dalam Pembiasaan Salat: Studi Analisis Hadis Riwayat Tirmidzi No. Indeks 407 - Evinda Aisyah,; Al-Amini, Muhammad Aben; Apriyanti, Tri Maulidya (Tasamuh: Jurnal Studi Islam, 2024)
This article aims to analyze self-habituation in prayer based on the hadith narrated by Tirmidzi with index number 407. Self-habituation in praying is an important aspect in the life of a Muslim that can affect individual self-management. The research method used is a literature study approach and contextual understanding, with the focus of the main data source of the research on the analysis of the hadith written in the Tirmidzi History with index number 407. This research also uses additional data sources in the form of other literature related to prayer collected through Google Scholar. The results show that the importance of prayer habituation starting from the age of 7 years. Habituation describes an individual’s effort to consistently engage in prayer activites, which then leads to good self-management that can be implemented in individuals through their discipline in daily life.